Marketing Library Services in Selected Private Universities in Ghana - Lamptey, W.O. (University of Ghana, 2016)
Despite the huge investments made by libraries into building their collections, studies have shown that these collections remain underutilized. This situation, coupled with declining library budgets, as well as growing competition between libraries and other information providers, has compelled libraries to adopt effective marketing approaches in order to continually remain visible and relevant. The adoption of marketing in libraries has been found to bring about numerous benefits to libraries hence its increased adoption among libraries worldwide. This study investigated the attitudes of library staff towards the marketing of library services in selected private universities, available marketing strategies and plans, and how they are applied in the promotion of their services to patrons. A total of 21 professional and para-professional library staff from three private universities participated in the study. The main data collection instrument was semi structured interviews used to elicit information about their knowledge of marketing, existing marketing policies, attitudes towards marketing, strategies used in marketing and the challenges encountered in marketing of services and resources. Data gathered was analysed thematically. The findings revealed that the study participants are fully aware of benefits of inculcating marketing activities into their daily routines and were making efforts at making their users aware of their products and services with the use of various strategies including social media. Some of the challenges that hindered the success of marketing in the libraries are lack of funds, lack of knowledge of marketing techniques by staff and a lack of marketing policy to guide marketing in the libraries. Creation of marketing policies, organization of seminars on marketing for library staff as well as proactively advocating for more funds from the right people within the university community is suggested to improve marketing of their services and resources.
Theses (MPhil.) - University of Ghana, 2016